2015
DOI: 10.5137/1019-5149.jtn.12669-14.0
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic-assisted keyhole technique for hypertensive cerebral hemorrhage in elderly patients: a randomized controlled study in 184 patients

Abstract: The keyhole technique is a new minimally invasive surgical approach, and became a new trend in neurosurgery. Even if the indications for surgical drainage are still controversial, the criteria for the choice of a drainage technique are even less well established. Several groups developed minimally invasive clot removal techniques (2,6,13,18).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 14 publications
1
61
0
Order By: Relevance
“…The pooled analysis (Cho et al, 2006;Feng et al, 2016;Zhang et al, 2014) revealed no statistically difference in death between neuroendoscopic surgery and craniotomy (RR = 0.58, 95% CI 0.26-1.29; p = .18) ( Figure 2).…”
Section: Pooled Analysis Of Death After Neuroendoscopic Surgery Vermentioning
confidence: 99%
See 2 more Smart Citations
“…The pooled analysis (Cho et al, 2006;Feng et al, 2016;Zhang et al, 2014) revealed no statistically difference in death between neuroendoscopic surgery and craniotomy (RR = 0.58, 95% CI 0.26-1.29; p = .18) ( Figure 2).…”
Section: Pooled Analysis Of Death After Neuroendoscopic Surgery Vermentioning
confidence: 99%
“…Based on the criteria described in the methods, 206 irrelevant citations were further excluded based on review of titles and abstracts. Finally, a total of 3 RCTs (Cho et al, 2006;Feng, He, Liu, Yang, & Wang, 2016;Zhang et al, 2014) were included in this meta-analysis (Figure 1). The major characteristics of included studies are depicted in Table 1.…”
Section: Overview Of Literature Search and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, neuroendoscopic surgery can reduce the stretch on cerebral tissue and reduce operative injury in patients with a deep-seated cerebral hematoma. 30 The procedure is performed with a small scalp incision and bone flap.…”
Section: Discussionmentioning
confidence: 99%
“…Hematoma drainage surgery is generally performed in elderly patients with hypertensive or traumatic intracerebral hemorrhage,even in chronic subdural hematoma [1][2][3][4] . The original device was widely used in the hematoma drainage surgery treatment technique.…”
Section: Introductionmentioning
confidence: 99%